PRAKTIK JUAL BELI ONLINE DITINJAU DARI PERSPEKTIF HUKUM EKONOMI ISLAM PADA MAHASISWA IAI AL-AZIS ANGKATAN 2016 - Anisa Aksani; Irvan Iswandi; Ali Aminulloh (Melati Institute, 2023)
The rapid development of technology today drives people to find easier ways to make transactions, especially in buying and selling online or known as online shop. The purpose of the present study was to determine and understand online buying and selling practices on IAI AL-AZIS Students and the perspective of Islamic law in online buying and selling. The present study used field research by using observation and interview research methods. The sampling technique was purposive sampling, i.e., designate members of a particular population, carried out based on certain considerations based on the characteristics or characteristics of the population that has been known before. According to purposive sampling in this study the sample that the author used was 6 students for IAI AL-AZIS. The research results showed that: 1) The implementation of online buying and selling for students of the Az-Zaytun Indonesia Islamic Institute (IAI AL-AZIS) class of 2016 was carried out using various social media applications. The sellers promoted their wares using the social media accounts they used. 2) Buying and selling according to an Islamic economic perspective that is legally carried out is buying and selling that has fulfilled the pillars and conditions of buying and selling, namely the existence of a seller and a buyer, the existence of goods that are used as the object of buying and selling, and the presence of sighat or consent granted. In addition to this condition, it is no less important that the goods must comply with the terms of the buyer both in terms of shape and colors. If some of these conditions are met, then actually buying and selling in anyway is not a problem, it is still valid and permissible.